The effect of sprint exercise in hypoxia on muscle glycogen utilization - Kasai, N.; Tanji, F.; Ishibashi, A.; Ohnuma, H.; Takahashi, H.; Goto, K.; Suzuki, Y. (The Journal of Physical Fitness and Sports Medicine, 2018)
[Aims] To determine the effect of maximal sprint exercise in hypoxia on muscle glycogen content among competitive athletes. [Methods] Ten sprinters (height; 176.9 ± 1.9 cm, body weight; 66.9 ± 2.0 kg) performed two trials under either hypoxic (HYP, FiO2: 14.5%) or normoxic (NOR, FiO2: 20.9%) conditions. The exercise in each trial consisted of three sets of 30-s maximal sprint. Muscle glycogen content was measured using carbon magnetic resonance spectroscopy (MRS) in the vastus lateralis and vastus intermedius muscles before and after the exercise. Moreover, percutaneous oxygen saturation, blood lactate, metabolic responses and muscle oxygenation were evaluated. [Results] Mean power output did not show a significant difference between two trials (P > 0.05). Blood lactate concentrations were not significantly different between two trials (P > 0.05). Change in muscle glycogen content showed significant interaction (P = 0.01) and main effect for time (P < 0.01). Moreover, relative changes in muscle glycogen content between before and after exercise was significantly greater in the HYP trial than in the NOR trial (HYP; -43.5 ± 0.4 %, NOR; -34.0 ± 0.3 %, P < 0.01). [Conclusion] Maximal sprint exercise in hypoxia caused further decrement of muscle glycogen content compared with the same exercise under normoxia.